EVALUASI PROGRAM PENDAMPING DESA DI KABUPATEN BENGKALIS - Yuslaini, Nina; Juliana, Septa (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
This study aims to look at the Village Companion Program in Bengkalis Regency and this research was conducted using survey research methods, the level of exploration was descriptive and used qualitative data analysis. The researcher interviewed directly and in depth with the key informants who were considered to be most knowledgeable about the Village Companion Program by using purposive sampling technique. Practically, the results of this study are useful as information material for the Bengkalis Regency Government especially the Bengkalis District Community Empowerment Office and are expected to be a reference in making policy guidelines related to Village Facilitators in Bengkalis Regency in the future.